An investigation into SOP based contract dispute adjudication process - Loh, Yan Zhu (2017)
There was no definitive law in Singapore that helped the construction firms with their payment dispute before the enactment of Security Of Payment Act (SOP Act). Construction projects are usually large in scale and involve a huge amount of money. However, many law firms were unfamiliar with issues pertaining to construction work and payment dispute cases took a long and costly process. As a result, many small firms faced cash flow problems, which resulted in bankruptcy. The enactment of SOP Act came into operation on 1st April 2005 with a sole purpose to improve cash flow in the construction industry. Hence it is important to understand the Act to benefit from it to the fullest. This report will focus on the fundamental issue encountered by the lack of understanding of the Act. The chosen case studies will be discussed and analyzed in details with reference to the relevant case.